1991
DOI: 10.1037/0033-2909.109.3.400
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety disorders research with African Americans: Current status.

Abstract: Anxiety disorders are the most common psychiatric disorders in the general population of the United States. Recent findings indicate that the prevalence of certain anxiety disorders may be higher in African Americans. In addition, anxiety disorders in African Americans may be manifested differently. Despite the high prevalence and the suggestion of different patterns of manifestation, a paucity of research exists on anxiety disorders in this population. This may be due in part to the pattern of help-seeking be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
171
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(180 citation statements)
references
References 80 publications
7
171
2
Order By: Relevance
“…The fears assessed in this study centered around the use of other persons' property (e.g., towels, utensils, dishes), animals, weather (lightning and thunder), and people (dentists, teachers, policemen, etc.). Neal and Turner (1991) suggested that the African-American children in this study reported more fears because many of the fear eliciting stimuli (e.g., using other persons' property) reflected the real hostility directed toward African-Americans in the late 1950s. It is possible that such results might not be obtained today.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…The fears assessed in this study centered around the use of other persons' property (e.g., towels, utensils, dishes), animals, weather (lightning and thunder), and people (dentists, teachers, policemen, etc.). Neal and Turner (1991) suggested that the African-American children in this study reported more fears because many of the fear eliciting stimuli (e.g., using other persons' property) reflected the real hostility directed toward African-Americans in the late 1950s. It is possible that such results might not be obtained today.…”
mentioning
confidence: 76%
“…In fact, among children from lower socioeconomic backgrounds with PTSD, 21.1% were African-American and only 3.4% were white. Neal and Turner (1991) have pointed out that African-Americans from low socioeconomic backgrounds may be at greater risk for the development of PTSD because of the greater number of stressors (e.g., crime, abuse, poverty) encountered by AfricanAmericans from low socioeconomic communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Neal and Turner's (1991) review of research on anxiety disorders among African Americans prompted the following statement:…”
mentioning
confidence: 99%